Usapan Tanpa Berpikir? Systematic Riview tentang Konten Edukasi TikTok 2020-2025: TikTok and the Critical Thinking Skills of the Young Generation: Systematic Literature Review 2020-2025 - Siti Masadatul Idohal Jamilah (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2026)
TikTok, a highly popular social media platform with 1.088 billion users worldwide, allows users to consume and create short-form video content. While the platform offers various benefits such as entertainment and creativity, concerns have arisen that excessive use may reduce critical thinking skills. Critical thinking involves the ability to analyse information deeply, evaluate arguments, and make reasoned decisions. On TikTok, users are often exposed to fast-paced, diverse information without sufficient opportunity for deep reflection. This study aims to systematically review the literature on TikTok's impact on critical thinking skills, particularly among adolescents and young adults. The study was conducted using the Systematic Literature Review (SLR) method, following the PRISMA 2020 guidelines, with a publication period from 2020 to 2025. The findings indicate that TikTok has potential as an educational medium to encourage critical thinking skills through community interaction, self-reflection, and evaluation of content credibility. However, passive consumption patterns and algorithmic bias can hinder the development of these skills, highlighting the need for critical digital literacy strategies to optimise the use of TikTok in the educational context.